THE NECESSITY OF REVISING ALGERIAN URBAN PLANNING REGULATIONS TO MEET USERS’ THERMAL COMFORT NEEDS: INTEGRATING THERMAL COMFORT AS A REQUIREMENT IN BUILDING PERMIT APPLICATIONS - A CASE STUDY - Toumi Fahmi; Tartar Nassima (International Journal of Innovative Technologies in Social Science, 2024)
The article addresses the importance of updating Algerian urban planning legislation to include thermal comfort standards in buildings, particularly in light of Executive Decree No. 15-19. Although this decree focuses on the engineering and administrative aspects of construction, it overlooks thermal comfort standards that ensure a comfortable and healthy environment for residents. According to international standards such as ISO 7730, details about temperature, humidity, and ventilation should be included in the design stages to ensure thermal comfort. However, Algerian legislation lacks these standards, leading to uncomfortable environments inside buildings. The article recommends amending the executive decree to incorporate thermal comfort standards into the building permit procedures, with the need to train architects and designers on applying these standards. Legislative updates will improve the quality of life in buildings and enhance their energy efficiency, contributing to their sustainability.